2009
DOI: 10.1016/j.exger.2009.02.013
|View full text |Cite
|
Sign up to set email alerts
|

The nurse’s load: Early-life exposure to brood-rearing affects behavior and lifespan in honey bees (Apis mellifera)

Abstract: Long-lived honey bees (Apis mellifera) develop in fall. This pattern may be explained by reduced nurse loads. When the amount of brood in colonies declines as a function of adverse foraging conditions, adult bees build up surplus nutrient stores that include vitellogenin, a behavioral affector protein that also can increase lifespan. Although the seasonal reduction in exposure to nursing tasks predictably results in vitellogenin accumulation, the assumption that long-lived adults thereby develop is confounded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 30 publications
(49 reference statements)
3
59
1
Order By: Relevance
“…However, the documented relation between behavior and life expectancy is correlative. Behavior may influence life expectancy (Rueppell et al 2007;Amdam et al 2009), but remaining life expectancy may also be a determinant of social behavior (Woyciechowski and Kozlowski 1998;Woyciechowski and Moron 2009;Kuszewska and Woyciechowski 2013). Regardless of causality, we also found evidence for an interaction between the social environment and the relation between social behavior and life expectancy.…”
Section: Discussionsupporting
confidence: 50%
“…However, the documented relation between behavior and life expectancy is correlative. Behavior may influence life expectancy (Rueppell et al 2007;Amdam et al 2009), but remaining life expectancy may also be a determinant of social behavior (Woyciechowski and Kozlowski 1998;Woyciechowski and Moron 2009;Kuszewska and Woyciechowski 2013). Regardless of causality, we also found evidence for an interaction between the social environment and the relation between social behavior and life expectancy.…”
Section: Discussionsupporting
confidence: 50%
“…This outcome supports our hypothesis that worker longevity potential, which translates into colony-level survival capability (Amdam and Omholt, 2002), is influenced by primer brood pheromone rather than the nurse load placed on workers. It has already been proposed that brood rearing shortens worker life and can lead to colony deaths in winter (Eischen et al, 1984;Omholt, 1988;Fluri and Imdorf, 1989;Amdam and Omholt, 2002) but the cause-effect relationship was previously explained by the metabolic costs of caregiving (Amdam et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the diutinus bees' physiology of extreme longevity could develop because less vitellogenin was lost to the production of brood food (Amdam and Omholt, 2002;Amdam et al, 2009). This proposition builds on previous work by Omholt (Omholt, 1988), who suggested that the nurse load of young honeybee workers affects longevity: a low nurse load can increase lifespan whereas a high nurse load has the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that responders (defined as individuals that show elevated ecdysteroid titers in the presence of QMP) and non-responders (individuals that do not show elevated titers in the presence of QMP) possibly represent different genotypes but may also reflect differences in epigenetic factors. The pheromone response threshold has been previously shown to be influenced by individual differences such as ovary size, social behavior, and age of exposure (Amdam et al 2009;Pankiw and Page Jr 1999;Traynor et al 2014;Vergoz et al 2009). A study in which responses to QMP presentation were observed in caged workers on the first 8 days of adult life revealed colony-level and individual differences in performance of the QMP-evoked retinue response, as well as differences in QMP-evoked brain gene expression profile (Kocher et al 2010).…”
Section: Social Modulation Of Qmp Effects On Ecdysteroid Titersmentioning
confidence: 99%